SEXUAL DISORDERS IN WOMEN DEPENDING ON AGE - Kayumova, Dilrabo T. (International Journal of Psychosocial Rehabilitation, 2020)
In order to assess the sexual functioning of the surveyed 1686 women from reproductive age to postmenopause (19-70 years).A semi-structured interview method was used in which women answered questions regarding her libido, changes in her sex life, and the presence of a sexual partner. Libido changes were noted by more than half of women of all age groups - from 52.6 to 64%, while significantly lowering of libido was observed in perimenopausal women - in 270 (42.1%) and its absence in women in peri- 112 (17.4%) and postmenopause - in 67 (26.2%). High rates of sexual dysfunction in peri- and postmenopausal disease correlate with functional, estrogen- deficient, psychological factors, as well as the absence of a sexual partner.